The complexities and caveats of lineage tracing in the mammary gland. Issue 1 (December 2016) - Rios, Anne; Fu, Nai; Cursons, Joseph; Lindeman, Geoffrey; Visvader, Jane
Abstract Lineage tracing is increasingly being utilised to probe different cell types that exist within the mammary gland. Whilst this technique is powerful for tracking cells in vivo and dissecting the roles of different cellular subsets in development, homeostasis and oncogenesis, there are important caveats associated with lineage tracing strategies. Here we highlight key parameters of particular relevance for the mammary gland. These include tissue preparation for whole-mount imaging, whereby the inclusion of enzymatic digestion can drastically alter tissue architecture and cell morphology, and therefore should be avoided. Other factors include the scoring of clones in three dimensions versus two dimensions, the timing of induction, and the marked variability in labelling efficiency that is evident not only between different mouse models harbouring a similar gene promoter but also within a given strain and even within a single mammary gland. Thus, it becomes crucial to visualise extensive areas of ductal tissue and to consider the intricacies of the methodology for lineage tracing studies on normal mammary development and on potential 'cells of origin' of cancer.